Suplementação com levedura autolisada melhora eficiência de fagócitos sanguíneos e reduz pneumonias em novilhos terminados em confinamento - Garbossa, Gabriela (2021)
The objective was to evaluate whether dietary supplementation with autolyzed yeast influences immunity and respiratory health in feedlot cattle. A randomized longitudinal experimental trial was conducted with 36 steers (Nelore X Angus) for 106 days: control (n=10): diet without yeast; Y4 (n=12): yeast diet (4 g per animal per day); and Y7 (n=7): yeast diet (7 g per animal per day). On days 0, 14, 42, 70, and 105, blood counts, leukocyte oxidative metabolism, and serum haptoglobin were evaluated to determine immune status, and the health of the respiratory tract was evaluated by nasal secretion frequency and orbital temperature. On slaughter day, a lung evaluation was performed. On days 42, 70 and 105 of feedlot finishing, the treated animals showed increased neutrophil oxidative metabolism (D42 P=0.04; D70 P=0.02 e D105 P=0.10) compared to the control group. These animals had a lower frequency of nasal secretion (D70 Y4 g and Y7g P=0.001; D105 Y4 g P=0.001) and a lower orbital temperature (D105 Y4 g P=0.04). These immune increments promoted less pneumonia in the treated groups (P = 0.05) and also, with less severity (P = 0.01), allowing us to infer that the autolyzed yeast fed a diet in both doses (4 g and 7 g) improves innate immunity and respiratory tract health of feedlot cattle.